High‐resolution loss of heterozygosity screening implicates PTPRJ as a potential tumor suppressor gene that affects susceptibility to non‐hodgkin's lymphoma1. Issue 5 (23rd January 2013) - Aya‐Bonilla, Carlos; Green, Michael R.; Camilleri, Emily; Benton, Miles; Keane, Colm; Marlton, Paula; Lea, Rod; Gandhi, Maher K.; Griffiths, Lyn R.
Abstract We employed a Hidden‐Markov‐Model (HMM) algorithm in loss of heterozygosity (LOH) analysis of high‐density single nucleotide polymorphism (SNP) array data from Non‐Hodgkin's lymphoma (NHL) entities, follicular lymphoma (FL), and diffuse large B‐cell lymphoma (DLBCL). This revealed a high frequency of LOH over the chromosomal region 11p11.2, containing the gene encoding the protein tyrosine phosphatase receptor type J (PTPRJ). Although PTPRJ regulates components of key survival pathways in B‐cells (i.e., BCR, MAPK, and PI3K signaling), its role in B‐cell development is poorly understood. LOH of PTPRJ has been described in several types of cancer but not in any hematological malignancy. Interestingly, FL cases with LOH exhibited down‐regulation of PTPRJ, in contrast no significant variation of expression was shown in DLBCLs. In addition, sequence screening in Exons 5 and 13 of PTPRJ identified the G973A (rs2270993), T1054C (rs2270992), A1182C (rs1566734), and G2971C (rs4752904) coding SNPs (cSNPs). The A1182 allele was significantly more frequent in FLs and in NHLs with LOH. Significant over‐representation of the C1054 (rs2270992) and the C2971 (rs4752904) alleles were also observed in LOH cases. A haplotype analysis also revealed a significant lower frequency of haplotype GTCG in NHL cases, but it was only detected in cases with retention. Conversely, haplotype GCAC was over‐representated in cases with LOH. Altogether, these results indicate that the inactivation of PTPRJ may be a common lymphomagenic mechanism in these NHL subtypes and that haplotypes in PTPRJ gene may play a role in susceptibility to NHL, by affecting activation of PTPRJ in these B‐cell lymphomas. © 2013 Wiley Periodicals, Inc.